2012
DOI: 10.2527/jas.2011-4486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeder design and changing source of water to a location separate from the wet-dry feeder at 4 or 8 weeks before harvest on growth, feeding behavior, and carcass characteristics of finishing pigs1,2

Abstract: Our objectives were to compare a conventional dry (5-space, 152.4-cm-wide) and a wet-dry (double-sided, each side = 38.1-cm-wide single space) feeder and to determine if changing the source of water to a location separate from a wet-dry feeder would result in improved G:F and carcass characteristics. Water supply to the wet-dry feeder was shut off and the cup waterer was turned on in 8 pens at 8 (d 69) or 4 (d 97) wk prior to harvest. For the remaining 8 wet-dry feeder pens, the feeder provided the sole water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…one pig round in one fattening farm). It should be noted that the feeding behaviour of pigs at the daily level is known to be influenced by many environmental and pig factors, such as feed(er) type 72 , lighting regime 40 , season 73 , pig gender 74 and breed 67 , 75 , an influence that is likely to extrapolate to diurnal feeding behaviour. Future research should explore to what extent such environmental and pig factors influence the individual and temporal differences in pig circadian rhythms and diurnal patterns in feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…one pig round in one fattening farm). It should be noted that the feeding behaviour of pigs at the daily level is known to be influenced by many environmental and pig factors, such as feed(er) type 72 , lighting regime 40 , season 73 , pig gender 74 and breed 67 , 75 , an influence that is likely to extrapolate to diurnal feeding behaviour. Future research should explore to what extent such environmental and pig factors influence the individual and temporal differences in pig circadian rhythms and diurnal patterns in feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…La alimentación húmeda incrementó también en 14 % la ganancia de peso y en 8 % la eficiencia alimenticia. La mayor GDP de cerdos AH, como el observado en el presente experimento, concuerda con los resultados reportados en cerdos de finalización (24) y cerdos en crecimiento-finalización alimentados con dieta húmeda durante 90 días (25) . En conjunto, estos resultados indican que la alimentación húmeda de cerdos expuestos a condiciones de temperatura ambiente elevada podría mejorar no solamente el consumo de alimento sino también la eficiencia en la utilización del alimento.…”
Section: Discussionunclassified
“…Los pesos de CC y CF mayores en los cerdos con AH registrados en el presente estudio, concuerdan con otros resultados previamente publicados (24) , en los que se reportó un mayor peso de la canal caliente, y rendimiento, aunque similar profundidad de grasa dorsal en cerdos alimentados con dieta húmeda, indicando esto la posibilidad de tener una influencia positiva de la alimentación húmeda en las características de la canal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…By testing a wide variety of feeders, Gonyou and Lou 5 found that wet-dry feeders consistently produced pigs with higher ADG and ADFI than dry feeders, indicating the improved productivity was likely due to the provision of water at the feeder. Bergstrom et al 16 demonstrated that the benefit of wet-dry feeders to improve ADG in pigs was diminished when the same wet-dry feeders were used as dry feeders (water source removed). An interactive effect between feed form and water availability in the feeder on ADG and ADFI in growing pigs was observed in the current study, that is, wet-dry feeders increased ADG and ADFI when pigs were fed mash diets, but not when pigs were fed pelleted diets.…”
Section: Discussionmentioning
confidence: 99%